The mere exposure effect depends on an odor’s initial pleasantness - Delplanque, Sylvain; Coppin, Géraldine; Bloesch, Laurène; Cayeux, Isabelle; Sander, David (Frontiers in Psychology, 2015)
The mere exposure phenomenon refers to improvement of one’s attitude toward an a priori neutral stimulus after its repeated exposure. The extent to which such a phenomenon influences evaluation of a priori emotional stimuli remains under-investigated. Here we investigated this question by presenting participants with different odours varying in a priori pleasantness during different sessions spaced over time. Participants were requested to report each odour’s pleasantness, intensity, and familiarity. As expected, participants became more familiar with all stimuli after the repetition procedure. However, while neutral and mildly pleasant odours showed an increase in pleasantness ratings, unpleasant and very pleasant odours remained unaffected. Correlational analyses revealed an inverse U-shape between the magnitude of the mere exposure effect and the initial pleasantness of the odour. Consequently, the initial pleasantness of the stimuli appears to modulate the impact of repeated exposures on an individual’s attitude. These data underline the limits of mere exposure effect and are discussed in light of the biological relevance of odours for individual survival.